Effectiveness of Diethanolamine (DEA) Addition on Band Gap Value of SnO2 by Using Sol-Gel Methods - Patriela, Miftah; Sanjaya, Hary (Darul Yasin Al Sys, 2024)
The need for electrical energy is increasing with the increase in the economy and population in Indonesia. Fossil energy sources are used as fuel to produce electrical energy and will run out if used continuously. Fossil energy sources can be replaced by using New Renewable Energy (NRE) to meet national electrical energy needs. The purpose of adding additives in this study is to observe the effectiveness of the addition of DEA on the band gap value, crystal phase, and surface morphology on SnO2. In this study using the sol-gel method for the synthesis of SnO2. The sol-gel method is the conversion of monomers into colloidal solutions (sol) which serve as precursors for integrated networks (gels) either discrete particles or network polymers. SnO2 nanomaterials will be characterized by UV-DRS Spectrophotometer. The results of characterization of SnO2 nanomaterials with the addition of Diethanolamine additives as much as 1.5 mL have obtained a band gap value of 3.60 eV.